Maternal Amino Acid Profiles to Distinguish Constitutionally Small versus Growth-Restricted Fetuses Defined by Doppler Ultrasound: A Pilot Study - Porter, Anne C.; Gumina, Diane L.; Armstrong, Michael; Maclean, Kenneth N.; Reisdorph, Nichole; Galan, Henry L.; Stabler, Sally P.; Bailey, Beth A.; Hobbins, John C.; Hurt, K. Joseph (American Journal of Perinatology, 2020)
Objective Fetuses measuring below the 10th percentile for gestational age may be either constitutionally small for gestational age (SGA) or have pathologic fetal growth restriction (FGR). FGR is associated with adverse outcomes; however, identification of low-risk SGA cases is difficult. We performed a pilot study evaluating maternal markers of pathologic FGR, hypothesizing there are distinct amino acid signatures that might be used for diagnosis and development of new interventions.Study Design This was a cohort study of healthy women with sonographic fetal estimated fetal weight <5th percentile divided into two groups based upon umbilical artery (UmA) Doppler studies or uterine artery (UtA) Doppler studies. We collected maternal blood samples prior to delivery and used ion pair reverse phase liquid chromatography-mass spectrometry or gas chromatography-mass spectrometry to assess 44 amino acids.Results Among 14 women included, five had abnormal UmA, and three had abnormal UtA Doppler results. Those with abnormal UmA showed elevated ornithine. Those with abnormal UtA had lower dimethylglycine, isoleucine, methionine, phenylalanine, and 1-methylhistidine.Conclusion We found several amino acids that might identify pregnancies affected by pathologic FGR. These findings support the feasibility of future larger studies to identify maternal metabolic approaches to accurately stratify risk for small fetuses.
Keywords: amino acid; fetal Doppler velocimetry; fetal growth restriction; uterine artery